Respuesta :
Answer:-3([tex]x{2}-2x+3[/tex])
Step-by-step explanation:
[tex]-3x{2}+6x-9[/tex]
firstly we should find the common factor between [tex]-3x{2}[/tex] , 6x and -9, the common between them is -3
-3([tex]x{2}-2x+3[/tex])
and ([tex]x{2}-2x+3[/tex]) cannot factorize
-
Answer:
−3(x2 − 2x + 3).
Step-by-step explanation:
Given the equation:
−3x2 + 6x − 9
-3x2
Factors:
= 1, 3
+6x
Factors:
= 1, 2, 3
-9
Factors:
= 1, 3, 3
The common factor in the 3 terms are, 1 and 3.
Therefore,
= 3(−x2 + 2x − 3)
= -3(x2 - 2x + 3)